A high‐performance cell‐phone based polarized microscope for malaria diagnosis. Issue 5 (13th February 2023) - Yu, Zhenfang; Li, Yunfei; Deng, Lin; Luo, Bing; Wu, Pinghui; Geng, Dongxian
Abstract: We present a cell‐phone based polarized microscope for diagnosing malaria through hemozoin recognition over a wide field‐of‐view (FOV) accompanied with decent image performance. The system is constructed based on attachment method using a lens assembly as objective, two mobile phones and two linear polarizers. A 0.92 μm resolution across a FOV of 3.27 mm × 3.27 mm with high imaging quality is realized, demonstrating an increased resolving power, four times improvement in FOV and better imaging quality over mobile‐optical‐polarization imaging device. Importantly, we also demonstrate it has capability of recognizing hemozoin within the sample for malaria diagnosis by imaging malaria‐infected blood samples with similar sensitivity comparable to Leica microscopy. It is more compact, portable, and insensitive to alignment, making it highly suitable for malaria detection in a portable, easy to setup and use way in low‐resource areas. Abstract : Malaria continues to a life‐threatening disease endemic to many remote and low‐resource areas. Here, we report a high‐imaging performance polarized microscope based on cell‐phone for easily discerning malaria pigment or hemozoin at low magnification and reduce the requirement of an expertly trained technicians. This microscope represented herein has the potential application of malaria detection in a portable, easy to setup, and use way in low‐resource areas.